Upaya Ustadz dalam Meningkatkan Kedisiplinan Santri di Pondok Modern Darul Hikmah Tulungagung: Efforts of Islamic Teachers to Improve the Discipline of Students at Darul Hikmah Modern Islamic Boarding School, Tulungagung - M. Agung Lukman Septiansyah; Muhtadin, Muhammad Akhsanul; Munir, Muhammad Syahrul (Efektor, 2023)
The main topic of discussion in this study is how the ustadz's efforts in improving the religious discipline of students at the Darul Hikmah Tulungagung Modern Islamic Boarding School and how the ustadz's efforts in increasing the discipline of students in Arabic and English there. This study uses a qualitative descriptive method, including data collection through observation, documentation, and interviews, as well as data reduction, presentation, and verification. This study also checked the validity of the data through triangulation of sources, techniques and time, extension of research and persistence of researchers. The findings of this study indicate that the ustadz's efforts in improving the religious discipline of students in various programs, such as the five daily prayers in congregation, reading the Qur'an, sunnah prayers, remembrance after the five daily prayers, shiyam Ramadhan, 'arafah and tathawwu' and various kinds methods namely authoritarian, permissive, and responsible, and ustadz efforts to improve the discipline of students in Arabic and English with the forms of discipline muhadharah, muhadatsah, division of vocabulary, mandatory communication using two languages and listening and there are also various ways, namely authoritarian, permissive and responsible freedom.